2023
DOI: 10.3389/fcell.2023.1174688
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted dynamic amplitude of low-frequency fluctuations in patients with active thyroid-associated ophthalmopathy

Abstract: Purpose: Thyroid-associated ophthalmopathy (TAO) is an autoimmune disease that affects the orbit and is the most prevalent extra-thyroidal complication of Graves’ disease. Previous neuroimaging studies have focused on abnormal static regional activity and functional connectivity in patients with TAO. However, the characteristics of local brain activity over time are poorly understood. This study aimed to investigate alterations in the dynamic amplitude of low-frequency fluctuation (dALFF) in patients with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Conversely, a signi cant decrease in dEC values was found from L-PoCG to L-V1. In a study by Wen et al 33 , an increase in dALFF value was reported in the SPG of patients with active thyroid-associated ophthalmopathy. This nding was postulated to be associated with delayed visuospatial information processing.Wu et al 34 discovered a decrease in FC values of the IPL among patients with asthma, potentially in uencing attention and executive function.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, a signi cant decrease in dEC values was found from L-PoCG to L-V1. In a study by Wen et al 33 , an increase in dALFF value was reported in the SPG of patients with active thyroid-associated ophthalmopathy. This nding was postulated to be associated with delayed visuospatial information processing.Wu et al 34 discovered a decrease in FC values of the IPL among patients with asthma, potentially in uencing attention and executive function.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, the support-vector machine (SVM) is a supervised machine learning technique that seeks to maximize the margin to sort input points into classes in a high-dimensional space (Pereira et al, 2009). The method of combining SVM and dALFF to analyze changes in brain activity in various diseases has been a research hotspot in recent years, such as comitant exotropia (Chen et al, 2022) and active thyroidassociated ophthalmopathy (Wen et al, 2023) and SVM has high accuracy in distinguishing patients from healthy populations. In the present study, we tested two hypotheses: (1) RD patients exhibit greater temporal variability compared with healthy controls (HCs); and (2) dALFF values are sensitive biomarkers that can distinguish RD patients from HCs.…”
Section: Introductionmentioning
confidence: 99%